2022
DOI: 10.1177/09603271221126487
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effects of nerolidol through promoting insulin receptor signaling in high-fat diet and low dose streptozotocin-induced type 2 diabetic rats

Abstract: The present study was designed to investigate the antidiabetic effect of nerolidol on high-fat diet and streptozotocin-induced diabetic rats. Type 2 diabetes was induced in animals by feeding them a high-fat diet for 4 weeks and administering a single intraperitoneal dose of streptozotocin (35 mg/kg body weight). Diabetic rats were treated with nerolidol (25 mg/kg BW) for 28 days. Results showed that nerolidol treatment significantly reduced ( p < 0.05) the level of elevated glucose, glycosylated hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Moreover, it was able to reduce oxidative stress markers and enhanced and activated glucose transporter-4 in skeletal muscle cells thereby improving insulin transport. 70 Hence, the antidiabetic properties of nerolidol can be further explored and that our results suggest that glucokinase can be a potential target for validation. Human ERK1 belongs to the mitogen-activated protein kinases (MAPK).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, it was able to reduce oxidative stress markers and enhanced and activated glucose transporter-4 in skeletal muscle cells thereby improving insulin transport. 70 Hence, the antidiabetic properties of nerolidol can be further explored and that our results suggest that glucokinase can be a potential target for validation. Human ERK1 belongs to the mitogen-activated protein kinases (MAPK).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it might also be a notable contributor to the antidiabetic effect reported in our study. Moreover, some of the compounds reported were previously associated with antidiabetic properties including, humulene [43], Caryophyllene [44], Nerolidol [45], Farnesol [46], and 2-Chloropropionic acid, octadecyl ester [47].…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…As a result, high glucose and glycated hemoglobin levels were reduced. In addition, the study reported that during the use of nerolidol, liver integrity was preserved, and the regulation of insulin-dependent glucose transport was improved in skeletal muscles due to the activation of GLU4 (Glucose transporter type 4) [ 87 , 88 ]. It is also worth mentioning that another substance with reported antihyperglycemic activity in the literature is caryophyllene, also identified in the essential oil of M. multiflora , which showed significant antidiabetic effects on glucose homeostasis in diabetic rats at a dose of 200 mg/kg (body weight) [ 89 ].…”
Section: Biological Activitiesmentioning
confidence: 99%